1994
DOI: 10.1143/jjap.33.5159
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Buffer Layers on Microstructural and Ferroelectric Characteristics of Sol-Gel Derived PbZrxTi1-xO3 Thin Films

Abstract: According to two estimated relations between the initial period and the dynamo-generated magnetic dipole field of pulsars, we calculate the statistical distributions of pulsar initial periods. It is found that proto-pulsars are very likely to have rotation periods between 20 ms and 30 ms, and that most of the pulsars rotate initially at a period < 60 ms. Our result supports the asymmetric neutrino emission model for pulsar kick.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…The mean grain size is 115 and 90 nm and average roughness is 8.1 and 3.2 nm for the single layer PZT and PZT/PMTT/PZT thin films, respectively. Indeed, it has been reported that the "rosette" texture is related to lead deficiency, which is induced by lead diffusion into the bottom electrode at the annealing temperature [12,13]. The improvement in surface texture of the sandwich structured thin film is attributed to the compensation for lead deficiency in the top PZT layer by the insertion of the PMTT interlayer, whereby the "rosette" structure is suppressed in the top PZT surface of the sandwich structured PZT/PMTT/PZT thin film.…”
Section: Methodsmentioning
confidence: 99%
“…The mean grain size is 115 and 90 nm and average roughness is 8.1 and 3.2 nm for the single layer PZT and PZT/PMTT/PZT thin films, respectively. Indeed, it has been reported that the "rosette" texture is related to lead deficiency, which is induced by lead diffusion into the bottom electrode at the annealing temperature [12,13]. The improvement in surface texture of the sandwich structured thin film is attributed to the compensation for lead deficiency in the top PZT layer by the insertion of the PMTT interlayer, whereby the "rosette" structure is suppressed in the top PZT surface of the sandwich structured PZT/PMTT/PZT thin film.…”
Section: Methodsmentioning
confidence: 99%
“…Since the deposition behavior of Pb oxide molecules is strongly dependent on the substrate temperature and the substrate material, the deposition characteristics of PZT films were studied by varying Pb(DPM) 2 phase of perovskite PZT rosettes embedded in microcrystalline pyrochlore matrix and the film deposited at 0.25 sccm shows large protruding grains that are likely to be related to the Pb-oxide phase. In contrast, PZT films deposited on the Pt/RuO 2 electrode have relatively small and uniform grains over the entire range of Pb(DPM) 2 flow rates, except for some protruding grains at 0.25 sccm.…”
Section: Effect Of Pt Template Layers On Deposition Characteris-mentioning
confidence: 99%
“…Fabrication methods that have mainly been employed for PZT films are sol-gel [2][3][4] or sputtering, 5,6) both of which have poor step coverage and therefore are not suitable for highdensity FRAM devices. Recently, attention has been given to the chemical vapor deposition (CVD) method, 7) which provides good step coverage, large area uniformity, and good film quality.…”
Section: Introductionmentioning
confidence: 99%
“…Some research groups have reported that a buffer layer plays a very important role in the growth of high-quality ferroelectric PZT films. 12,13) We reported that 2-nm-thick Ti buffer layers enhanced PZT nucleation processes and allowed the realization of fine and dense grain structures by sol-gel processing. 14) However, in PZT thin films prepared by sputtering, control of the PZT grain structure has not been realized with the use of a Ti buffer layer.…”
Section: Introductionmentioning
confidence: 99%